Long-term photopolarimetric variability of DD Ser - Belan, S.P.; Shakhovskoy, D.N. (Advances in Astronomy and Space Physics, 2013)
We present some results of UBVRI-photopolarimetric observations of DD Ser, a poorly studied and understood Ae-star. The long-term component of light variation is detected, with the period of about fifteen years. Variability of the degree and positional angle of linear polarization is observed as well. Analysis of correlation between photometric and polarimetric data shows that observed light minima are likely caused by variability of circumstellar extinction produced by dust.